A matéria tristaniana do ciclo do Pseudo-Boron, da Suite du Merlin à Demanda do Santo Graal - Laranjinha, Ana Sofia (2014)
The Pseudo-Robert de Boron cycle re-writes the Arthurian prose cycle adding to the Estoire del Saint Graal, Merlin (to which a long Suite is added) and Queste (considerably amplified) a Tristan en prose and, probably, a Lancelot. The composition of this cycle was possible thanks to a continuous process of rewriting: simultaneous or alternating writing of different romances, which grew in several phases that we can identify through the detection of stylistic and ideological features.